Self-Efficacy and Moral Education in Enhancing the Moral Development and Social Intelligence of Muslim Adolescents - Warsah, Idi; Morganna, Ruly; Warsah, Berliani Aslam Alkiromah; Warsah, Bizikrika Hably Hudaya (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2024)
This study explored the implementation of moral education in enhancing self-efficacy, moral development, and social intelligence among Muslim adolescents, along with its theoretical implications. Using a comprehensive literature review method, data sources included journals, books, and academic publications related to moral education and youth development. Data were collected through the identification, selection, and critical analysis of relevant literature. The findings indicate that moral education, emphasizing values such as honesty, justice, and responsibility, significantly enhances students' self-efficacy. Structured programs involving personal reflection, group discussions, and community service projects help students develop self-confidence, moral awareness, and ethical decision-making skills. A supportive environment and positive reinforcement also play crucial roles in promoting positive social interactions and social skills like empathy and cooperation. These findings support theories of moral development and Bandura's self-efficacy theory, highlighting the importance of direct experience, positive reinforcement, and social interaction in the development of social and moral skills. Structured moral education provides a strong foundation for students' personal and social development, preparing them to become ethical, confident, and adaptable individuals in society.